Analisis Pengaruh Piutang Tak Tertagih Terhadap Profitabilitas Pada Perusahaan CV. Anugrah Sriwijaya Sukses - Yapet Tanuma (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to analyse the effect of the ratio of arrears and collectors to return on assets at CV Anugrah Sriwijaya Sukses. This research is descriptive quantitative. Data were obtained through interviews with company leaders and employees related to the finance department and looking at financial report data for the 2017-2019 period. Data were collected using purposive sampling method and analysed using multiple linear regression. The findings evidence that partially, arrears have an effect on return on assets, and the ratio of collectors has no effect on return on assets. Simultaneously, the ratio of arrears and collectors simultaneously have a positive and significant effect on return on assets at CV Anugrah Sriwijaya Sukses.